Falciparum malaria-induced secondary hemophagocytic lymphohistiocytosis successfully treated with ruxolitinib. (November 2020) - Fuchs, André; Orth, Hans-Martin; Germing, Ulrich; Kondakci, Mustafa; Holtfreter, Martha; Feldt, Torsten; Jensen, Björn Erik-Ole; Häussinger, Dieter
Highlights: Secondary hemophagocytic lymphohistiocytosis (sHLH) is rare but life-threatening. sHLH can also be triggered by falciparum malaria. The optimal strategy for the diagnosis and treatment of sHLH in adults is not yet well defined. This article reports the successful treatment of sHLH after falciparum malaria with ruxolitinib. Ruxolitinib might be a promising, rapidly acting treatment option for severe sHLH. Abstract: JAK/STAT signaling plays a major role in the pathogenesis of secondary hemophagocytic lymphohistiocytosis. This case report on a critically ill patient with secondary hemophagocytic lymphohistiocytosis due to falciparum malaria treated successfully with ruxolitinib, demonstrates that JAK1/2 inhibition might be a promising treatment option for severe cases.